Poems for every season : a year of haiku, sonnets, and more - Westera, Bette (Eerdmans Books for Young Readers, 2026)
"Woodcut art and poems in various forms (haiku, rondel, limerick, sonnet, and more) celebrate the four seasons"-- Provided by publisher.